Verteilungsmuster von Spurenmetallen im glazialen Nordatlantik : Rekonstruktion der Nährstoffbilanz anhand von Cadmiumkonzentrationen in kalkschaligen Foraminiferen - Willamowski, Claudia (1999)
Benthic Cd/Ca and δ13 C-records along sediment cores from the northern North Atlantic and the Portuguese and Moroccan continental margins are used to trace water mass distribution patterns during the last glacial with special emphasis on glacial meltwater events ('Heinrich' events). Along the western Iberian continental margin and in the Gulf of Cadiz, water column profiles of cadmium, calcium and phosphate are combined to retrieve a regional Cd:P-correlation which represents tracer patterns in Mediterranean Outflow Water (MOW). Benthic Cd/Ca-ratios of surface-sediment samples are used to determine modern distribution coefficients ((Cd/Ca)foraminifera:(Cd/Ca)sea water) which, in turn, are used to infer water column paleo-cadmium (Cdw) concentrations from Cd/Ca-ratios of glacial-time benthic foraminifera. Cadmium and δ13 C values of intermediate-water sediment cores from different areas in the northern North Atlantic are compared. Data from the upper Portuguese and upper Moroccan continental margins document a strong MOW influence today. Modem benthic Cdw and δ13 C of the deeper Portuguese continental margin trace North Atlantic Deep Water (NADW), similar to benthic data from the northern North Atlantic. Glacial benthic Cd/Ca and δ13 C values from the upper Portuguese margin document an increased advection of glacial intermediate water (Glacial North Atlantic Intermediate Water, GNAIW; Duplessy et al., 1988), or Upper North Atlantic Deep Water (UNADW; Sarnthein et al., 1994). Data from the lower continental slope indicate an increased advection of Antarctic Bottom Water (AABW). At the upper Moroccan margin, glacial data are consistent with an advection of a mixture of AAIW and GNAIW/UNADW. The regional data distribution further indicates that the northern North Atlantic between 1500 and 3000 m water depth was as weil ventilated during the last glacial as today, whereas data from sediment cores from 1 to 2 km water depth imply a better glacial ventilation. Strongly reduced convection during glacial meltwater ...